The Potential of panHER Inhibition in Cancer - Wang, Xiaochun; Batty, Kathleen M.; Crowe, Philip J.; Goldstein, David; Yang, Jia-Lin (Frontiers in Oncology, 2015)
Purpose: Hyper activation of the HER (erbB) family receptors, HER 1-4, leads to up-regulation of the three vital signalling pathways: mitogen activated protein kinase, phosphoinositide 3-kinase/ AKT, and Janus kinase/ signal transducer and activator of transcription pathways. Blocking HER1/EGFR has a limited anticancer effect due to either secondary mutation e.g., T790M or by-pass signalling of other HER members. The emergence of an anti-panHER approach to blockade of these pathways as a cancer treatment may provide a solution to this resistance. This review aimed to provide an overview of the HER signalling pathways and their involvement in tumour progression and examine the current progress in panHER inhibition. Methods: Recent literature associated with HER signalling pathways and panHER inhibition was reviewed through PubMed and Medline database, followed by critical comparison and analysis. Results: Preclinical studies and clinical trials of panHER inhibitors show promising results, and the potential to improve patient outcomes in solid cancers. Conclusions: The use of panHER inhibitors in cancers with HER family hyper-activation, such as other epithelial cancers and sarcoma, is a new direction to research and has potential in clinical cancer therapy in the future.